Targeted panel sequencing in adult patients with left ventricular non‐compaction reveals a large genetic heterogeneity. Issue 3 (27th December 2018) - Richard, Pascale; Ader, Flavie; Roux, Maguelonne; Donal, Erwan; Eicher, Jean‐Christophe; Aoutil, Nadia; Huttin, Olivier; Selton‐Suty, Christine; Coisne, Damien; Jondeau, Guillaume; Damy, Thibaud; Mansencal, Nicolas; et al.
Abstract : Left ventricular non‐compaction (LVNC) is a cardiomyopathy that may be of genetic origin; however, few data are available about the yield of mutation, the spectrum of genes and allelic variations. The aim of this study was to better characterize the genetic spectrum of isolated LVNC in a prospective cohort of 95 unrelated adult patients through the molecular investigation of 107 genes involved in cardiomyopathies and arrhythmias. Fifty‐two pathogenic or probably pathogenic variants were identified in 40 patients (42%) including 31 patients (32.5%) with single variant and 9 patients with complex genotypes (9.5%). Mutated patients tended to have younger age at diagnosis than patients with no identified mutation. The most prevalent genes were TTN, then HCN4, MYH7, and RYR2 . The distribution includes 13 genes previously reported in LVNC and 10 additional candidate genes. Our results show that LVNC is basically a genetic disease and support genetic counseling and cardiac screening in relatives. There is a large genetic heterogeneity, with predominant TTN null mutations and frequent complex genotypes. The gene spectrum is close to the one observed in dilated cardiomyopathy but with specific genes such as HCN4 . We also identified new candidate genes that could be involved in this sub‐phenotype of cardiomyopathy. Abstract :